Responsabilidad social: ¿un regalo o un gasto necesario? Entre el buen gobierno corporativo y la determinación del impuesto a la renta - Benites Mendoza, Mónica (2014)
This paper seeks to contribute, through discussion, to the issue of costs related to social responsibility, a matter that has recently gained importance. In that sense, our intention is to examine to what extent such costs meet the criterion of causation, a necessary requirement to be deductible.